Colonic perforation following major burns: Experience from a burns center and a systematic review. Issue 6 (September 2021) - Fadel, Michael G.; Iskandarani, Mohamad; Cuddihy, Joshua; Jones, Isabel; Collins, Declan; Kontovounisios, Christos
Highlights: Colonic perforation following burns is a rare event. Systematic review of burns complicated by colonic perforation. Right-sided colonic perforations more common with a higher mortality rate. Colonic perforation mainly secondary to systemic effect of burn injury and sepsis. Abstract: Background: Major burns complicated by stress ulceration and perforation of the stomach or duodenum is a recognized clinical phenomenon. Colonic perforation in burns patients is not common, and the overall incidence, diagnosis, intervention undertaken and mortality is incompletely described in the literature. Method: We performed a systematic review of the literature on severe burns resulting in colonic perforation during the initial admission period. Relevant studies from January 1975 to June 2020 were retrieved from MEDLINE and EMBASE databases. Patient demographics, co-morbidities, total body surface area (TBSA) and anatomical region of burn, site of colonic perforation and management, nutrition, sepsis and microbiology, length of stay and overall outcome were extracted. We present a case series of five burns patients who had colonic perforations in our Specialist Burns Center. Results: We identified 54 studies, of which nine (two case series and seven case reports) met the inclusion criteria. Colonic perforation following burns was most common in middle-aged male patients with a proportion of patients having a history of mental health issues. In most cases, the TBSA associated with a colonic perforation was ≥30% (11/16 patients, 69%). Perforations mainly affected the right side of the colon (12/16 patients, 75%), usually occurring after the second week of admission (13/16 patients, 81%). Right-sided colonic perforations were associated with an increased mortality rate compared to left-sided perforations (42% vs 25%). Conclusions: The current literature is mainly limited to case series and case reports and confirms that colonic perforations in burns patients are rare. Colonic perforations are related to the systemic effect of burn injuries including sepsis and gastrointestinal stasis. We have identified patients who are at higher risk of developing colonic perforations and have described the common findings in these patients. Through greater awareness early diagnosis and prompt intervention may be achieved to improve outcomes and reduce associated morbidity and mortality.